2013
DOI: 10.1089/end.2013.0347
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Percutaneous Nephrostomy Tube During Ureteroscopy for Upper Ureter Stone Management

Abstract: URS for upper ureteral stones in patients with PCN produced superior surgical outcomes in terms of the success rate, operative time, and auxiliary procedure rate without increasing the complication rate. The presence of PCN with/without external irrigation during URS can be a beneficial factor to produce better outcomes of URS for the management of upper ureteral stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…Kwon et al . reported that draining the retrograde irrigation fluid through the PCN catheter can help decompress the renal pelvis and straighten the ureter portion above the stone, thereby reducing the risk of urinary tract infection, preventing stone migration, and providing a better view . Indeed, we maintained a clear view of the operative field throughout the entire procedure, and the patient did not experience postoperative fever.…”
Section: Discussionmentioning
confidence: 79%
“…Kwon et al . reported that draining the retrograde irrigation fluid through the PCN catheter can help decompress the renal pelvis and straighten the ureter portion above the stone, thereby reducing the risk of urinary tract infection, preventing stone migration, and providing a better view . Indeed, we maintained a clear view of the operative field throughout the entire procedure, and the patient did not experience postoperative fever.…”
Section: Discussionmentioning
confidence: 79%
“…In our study, to compare the outcomes between the antegrade and retrograde irrigation groups, patients who had to undergo PCN insertion because of ureter stone with suspected infection were excluded. A previous study used antegrade irrigation during retrograde ureteroscopy, which is a method similar to ours; 42 patients had PCN and antegrade irrigation was applied in 21 patients [14]. They found that, with antegrade irrigation method during retrograde ureteroscopy, fragmented stones could be more easily shifted from the proximal to the distal ureter.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, if percutaneous nephrostomy (PCN) has been performed before URS, the antegrade irrigation via PCN may increase stone-free rate and reduce the ancillary procedures, such as flexible ureteroscopy or percutaneous antegrade ureteroscopy. Nevertheless, to the best of our knowledge, only one clinical research where PCN was utilized during retrograde semirigid ureteroscopy (the irrigation fluid flowed via the PCN tube and not via the ureteroscope) was conducted [14]. It may be due to the facts that (1) PCN cases in the upper ureter stones are not common because PCN is generally considered in patients with intractable pain, suspicious infection, or deteriorating renal function; (2) surgeons may be concerned that the antegrade irrigation via PCN during URS may increase the infection rate.…”
Section: Introductionmentioning
confidence: 99%
“…During this period, at total of 1,519 patients were registered in our database. Inclusion criteria for the current study were as follows: i) upper ureter stones measuring 4 to 20 mm, ii) radiopaque calculi located within the ureter on simple X-ray within one month of treatment with no evidence of stone migration, and iii) the upper ureter is defined as the segment between the ureteropelvic junction and the superior margin of the sacroiliac joint, and the upper ureter stone is defined as the calculi in the upper ureter [ 12 ]. Patients without NCCT scans were excluded.…”
Section: Methodsmentioning
confidence: 99%